(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
The operation of a photovoltaic (PV) panels are influenced by its inclination angle with the horizontal surface. Thus, it must be inclined at a proper angle to raise the effectiveness of these panels. This research focuses on the computation of optimum slope angle of the PV panels in order to get the maximum incident solar radiation. Therefore, it is recommended to set the PV panels at fixed slope angle throughout the year to avoid the cost of sun tracking systems. In this research, an optimum slope angle of PV panels is investigated to get a maximum incident solar irradiance value using Bernard-Menguy-Schwartz model for some Iraq cities: Baghdad city (latitude of 33o22’N), Mosul city (latitude of 36o15’N), Zakho city (latitude of 37o10’N), and Samawah city (latitude of 31o15’N). The results showed that the optimum slope angle for these panels seems to be close to latitude of these cities.